A setup for synchrotron‐radiation‐induced total reflection X‐ray fluorescence and X‐ray absorption near‐edge structure recently commissioned at BESSY II BAMline. (1st April 2016) - Fittschen, U.; Guilherme, A.; Böttger, S.; Rosenberg, D.; Menzel, M.; Jansen, W.; Busker, M.; Gotlib, Z. P.; Radtke, M.; Riesemeier, H.; Wobrauschek, P.; Streli, C.
Abstract : The new setup for synchrotron‐radiation‐induced TXRF and TXRF‐XANES at BAMline BESSY II is described and characterized. Abstract : An automatic sample changer chamber for total reflection X‐ray fluorescence (TXRF) and X‐ray absorption near‐edge structure (XANES) analysis in TXRF geometry was successfully set up at the BAMline at BESSY II. TXRF and TXRF‐XANES are valuable tools for elemental determination and speciation, especially where sample amounts are limited (<1 mg) and concentrations are low (ng ml −1 to µg ml −1 ). TXRF requires a well defined geometry regarding the reflecting surface of a sample carrier and the synchrotron beam. The newly installed chamber allows for reliable sample positioning, remote sample changing and evacuation of the fluorescence beam path. The chamber was successfully used showing accurate determination of elemental amounts in the certified reference material NIST water 1640. Low limits of detection of less than 100 fg absolute (10 pg ml −1 ) for Ni were found. TXRF‐XANES on different Re species was applied. An unknown species of Re was found to be Re in the +7 oxidation state.